OCCURRENCE OF EGGS OF MYCTOPHIDAE IN THE SHELF REGION OFF MADRAS COAST - Girijavallabhan, K G (Indian Journal of Fisheries, 2011)
A descriptive account of the egg hitherto not reported from Bay of Bengalbelonging to the family Myctophidae is given.